Distribution and Cytokine Profile of Peripheral B Cell Subsets Is Perturbed in Pediatric IBD and Partially Restored During a Successful IFX Therapy. Issue 2 (18th March 2020) - Schnell, Alexander; Schwarz, Benedikt; Wahlbuhl, Mandy; Allabauer, Ida; Hess, Merlin; Weber, Sabine; Werner, Felix; Schmidt, Hannah; Rechenauer, Tobias; Siebenlist, Gregor; Kaspar, Sonja; Ehrsam, Christoph; et al.
Abstract: Background: The role of B cells in inflammatory bowel disease (IBD) is ambiguous, as B cells may have both pathogenic and protective functions in IBD. We studied B cell subsets before and after initiation of an anti-tumor necrosis factor alpha (anti-TNFα) therapy in pediatric IBD. The aim of the study was to examine the behavior of B cells in pediatric IBD patients undergoing an anti-TNFα therapy and, more specifically, to clarify their association with a successful or an unsuccessful infliximab (IFX) treatment. Methods: A total of N = 42 pediatric IBD patients (Crohn disease, n = 30; ulcerative colitis, n = 12) for whom an anti-TNFα therapy with and without a concomitant azathioprine (AZA) medication was administered were recruited. Fourteen healthy age-matched children served as control patients. Blood samples were collected before initiation of the anti-TNFα therapy, before the fourth infusion at the end of the induction phase, and after 6 and 12 months under therapy maintenance. Flow cytometry (CD20, CD27, CD38, CD138) and intracellular staining (interleukin 10 [IL10], TNFα, granzyme B) were performed. Responders to successful IFX therapy were classified exhibiting a fecal calprotectin level of below 100 µg/g or achieving levels of <10% of the baseline value at initiation than at the end of the 12-month follow-up period. Results: Before initiation of anti-TNFα therapy, flow cytometry revealed increased percentages of naïve B cells whereas transitional B cells were reduced compared with those in the healthy control patients. The IL10-producing B cells of both ulcerative colitis and Crohn disease patients were reduced at the initiation of IFX therapy, whereas TNFα-producing transitional CD24 hi CD38 hi B cells in ulcerative colitis patients were increased compared with those in healthy control patients. After 12 months of therapy, we detected a significant increase of IL10-producing transitional B cells in responding patients. The IFX trough levels in the responding patients showed a significant increase until 6 months after IFX initiation, attaining mean values of 9.9 µg/mL, whereas the IFX dosage was significantly lower than that in the nonresponding patients. The IFX trough levels in AZA-treated patients reached earlier therapeutic levels than in patients without AZA comedication, whereas during the course of the IFX therapy, comedication with AZA had no significant effect on the outcome. Conclusions: Attaining a normalization of IL10 production among CD24 hi CD38 hi B cells after 12 months of therapy may represent additional information about the reconstitution of a patient's immune system in responding patients. The achievement of an IFX trough level of 10 µg/mL at 6 months of treatment is associated with a successful anti-TNFα therapy. In addition, AZA comedication supports an earlier achievement of therapeutic IFX trough levels.